Paides et parthenoi : une mixité sexuelle juvénile pour des rites asexuels ? - Romain Roy (Genre, Sexualité et Société)
The terms of configuration of ritual practices in ancient Greece often show a partitioning of the categories of gender and age. However, the association of young boys (paides) and young girls (parthenoi) in specific contexts of worship seems to disturb that partitioning. If the traditional interpretation of these rituals as rites of initiation seems hard to bear, they nevertheless question the construction of gender. Indeed, the possibility of these ritual associations disappearing as boys and girls progress in the age scale, suggests that sexual practices are central in the normalized construction of these ritual relationships of gender. So, gender has to be seen as an ideal standard of sexuality, a standard which is only possible in the body of young Greeks, according to sex; thus expressing their specific ritual potential, as their worship meetings testify.